2004
DOI: 10.5840/beq200414212
|View full text |Cite
|
Sign up to set email alerts
|

The Imperfect Nature of Corporate Responsibilities to Stakeholders

Abstract: Abstract:In this paper, I specifically consider the issue of corporate governance and normative stakeholder theory. In doing so, I argue that stakeholder theory and responsibilities to non-shareholder constituencies can be made more intelligible by reference to Kant’s conception of perfect and imperfect duties. I draw upon Onora O’Neill’s (1996) work, Towards Justice and Virtue: A Constructivist Account of Practical Reasoning. In her text O’Neill underlines a number of relevant issues including: the integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
(10 reference statements)
0
23
0
1
Order By: Relevance
“…Although Donaldson and Dunfee (1999, p. 685) call out the importance of ''hypernorms'' universally due, in practice employee/followers are not equally treated as stakeholders (Lea, 2004). Evan and Freeman (1993) noted that in the balancing of claims of multiple stakeholders, management decisions must be made that required a compromise in valuing the stakes and outcomes.…”
Section: Stakeholder Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…Although Donaldson and Dunfee (1999, p. 685) call out the importance of ''hypernorms'' universally due, in practice employee/followers are not equally treated as stakeholders (Lea, 2004). Evan and Freeman (1993) noted that in the balancing of claims of multiple stakeholders, management decisions must be made that required a compromise in valuing the stakes and outcomes.…”
Section: Stakeholder Theorymentioning
confidence: 98%
“…(4) How am I valued? Treating stakeholders as normatively valued ends rather than as instrumental means presumes that an organization perceives its governance role from a principle-based or virtue ethics perspective (Lea, 2004). Schumann (2001) reported that moral relativism -an uncertain standard of what is right or wrong -existed in many business organizations, and with that uncertainty employees became uncomfortable about how they are valued compared to firm profitability.…”
Section: Follower Assumptions About Ethical Governancementioning
confidence: 99%
“…Researchers of both branches have raised a number of issues, such as which normative basis should be adopted for this approach? (Beekun and Badawi 2005;Burton and Dunn 1996;Etzioni 1998;Lea 2004;Wijnberg 2000), which agents are, or should be, given preferential treatment by the company? (Clarkson 1995;Cragg and Greenbaum 2002;Driscoll and Starik 2004;Mitchell et al 1997;Phillips et al 2003), how should the company balance the interests of its stakeholders?…”
Section: Who Were Stakeholders Initially?mentioning
confidence: 98%
“…According to Benders and Van Veen (2001), the increasing popularity of both CSR and CG generates some ambiguity in defining the confines of each. Other important contributions to the literature (Aguilera et al, 2006;Lea, 2004) also underscore the existence of complementarities between CG and CSR. In an attempt to conceptualize the relationship between CG, CSR and business ethics, Fassin and Van Rossem (2009) explore the distinctiveness and clarity in the perceptions that opinion leaders have concerning CG, CSR and business ethics, and the relationships that exist between them.…”
Section: The Cg-csr Nexus: Related Literaturementioning
confidence: 99%